A REVIEW ON HPLC METHOD DEVELOPMENT AND VALIDATION STUDIES OF COMBINED DOSAGE FORM OF IVACAFTOR AND TEZACAFTOR - MADDALA, SANDHYA MADHURI; KOLA, JAHNAVI PARVATHI; ILLA, SARIKA SUPRIYA (International Journal of Pharmacy and Pharmaceutical Sciences, 2025)
The establishment of reliable and precise analytical methodologies plays a critical role in pharmaceutical research, manufacturing processes, and quality assurance. These methods are essential not only for identifying active pharmaceutical ingredients (APIs) but also for detecting contaminants and unintended chemical entities that may enter drug formulations during the production process. Before an analytical method can be implemented in commercial pharmaceutical manufacturing, it must be thoroughly validated by the International Council for Harmonisation (ICH) guidelines to confirm its accuracy, precision, specificity, and reliability. Cystic fibrosis (CF) is a genetic disorder affecting the lungs, digestive, and reproductive systems, caused by mutations in the CFTR gene that result in the accumulation of thick, sticky mucus leading to respiratory and digestive complications. A key therapeutic strategy for CF involves combination therapy using Tezacaftor (TZR) and Ivacaftor (IVR), two drugs that target the underlying genetic defect and improve the function of the CFTR protein. This article reviews the development and validation of analytical and bioanalytical methods for Tezacaftor and Ivacaftor, using Ultra and High-Performance Liquid Chromatography (UPLC/HPLC), and advanced techniques like LC-Tandem Mass Spectrometry (LC-MS/MS). The review outlines key steps in method development, including optimisation of chromatographic parameters and validation processes necessary to ensure that the drugs meet the required standards of purity, potency, and quality. Emphasis is placed on the importance of reliable HPLC and bioanalytical methods in supporting the production of these essential CF therapies while adhering to stringent regulatory requirements.